A Field Evaluation of Selected Beach-Cleaning Techniques - Owens, Edward H.; Robson, Wishart; Foget, Carl R. (ARCTIC, 1987)
A series of experiments was conducted to evaluate selected countermeasures for the cleanup of oil on remote beaches. These experiments formed part of the Baffin Island Oil Spill (BIOS) Project, which was conducted at Cape Hatt, N.W.T., between 1980 and 1983. An isolated lagoon was selected with a series of segregated bays that could be used for discrete experiments with control and countermeasure plots. Intertidal control plots were established in 1980 at an exposed site and at a relatively sheltered location. The oil on the exposed intertidal control plot was removed rapidly by natural processes so that subsequent attention was focused on low wave energy sites. Countermeasure experiments were conducted in 1981 in the intertidal zone at a relatively sheltered site and in 1982 in the intertidal and backshore zones at a very sheltered beach. At each of these two locations, control and countermeasure plots were duplicated using an aged Lagomedio crude oil and a water in aged Lagomedio emulsion. Countermeasures were selected for testing on the basis of existing experimental or practical knowledge and the applicability to remote or arctic beach environments. The selected techniques were incendiary combustion, mechanical mixing, chemical dispersion, solidifying and low-pressure flushing. .Key words: countermeasures, dispersants, flushing, incendiary devices, mixing, natural cleaning, oil spill, shoreline, solidifying agent Mots clés: mesures d’intervention, agents de dispersion, lavage à grande eau, mécanismes incendiaires, brassage, nettoyage naturel, déversement depétrole, littoral, agent solidifiant